Evaluation of Bus Networks in China: From Topology and Transfer Perspectives - Hui Zhang; Peng Zhao; Yinhai Wang; Xiangming Yao; Chengxiang Zhuge (Discrete Dynamics in Nature and Society)
With the development of the public transportation, bus network becomes complicated and hard to evaluate. Transfer time is a vital indicator to evaluate bus network. This paper proposed a method to calculate transfer times using Space P. Four bus networks in China have been studied in this paper. Some static properties based on graph theory and complex theory are used to evaluate bus topological structure. Moreover, a bus network evolution model to reduce transfer time is proposed by adding lines. The adding method includes four types among nodes with random choice, large transfer time, degree, and small degree. The results show that adding lines with nodes of small degree is most effective comparing with the other three types.